The Reality of Employing Cloud Computing in Education: (A Field Study at the Higher Institute of Science and Technology ) - Marym Omar Said Latrsh (Journal of Scientific and Human Dimensions, 2026)
This study aims to identify the reality of employing cloud computing in the educational process for higher education students at the Higher Institute of Science and Technology in Kikla. The study adopted the descriptive approach using the social survey method, as it is appropriate for the nature of the study. A questionnaire was used as the primary tool for data collection, distributed to a sample of (84) male and female students. The results showed that the level of employing cloud computing in the educational process was moderate, while its perceived importance was high from the students’ perspective, reflecting a gap between perception and practice. The results also revealed significant challenges hindering actual use, most notably the high cost of some cloud services and a lack of the knowledge or training necessary to use them efficiently. These findings suggest the necessity of adopting educational and training strategies that contribute to enhancing the actual use of cloud computing by developing infrastructure, increasing students’ digital competencies, and systematically integrating these applications into educational practices.